On the simulation of radar echo intensity from the ice sheet in the East Antarctica (IV) (abstract) - Nishitsuji, Akira; Hoshiyama, Mitsuo; Nishio, Fumihiko; Wada, Makoto; Watanabe, Okitsugu (National Institute of Polar Research, 1989)
P(論文) We have grouped the radar echoes from the ice sheet near the Sirase Glacier in East Antarctica, and succeeded in the simulation of some kind radar echoes. And, on the radar echo having the standard echo form, we have found the features to be as follows. (1) The density in the ice sheet is the constant ( departmental bulletin paper